Endovascular Repair of Thoracoabdominal Aortic Aneurysm: A Brief Review - Tohme, Scarlett; Newman, Joshua; Yu, Pey-Jen (International Journal of Angiology, 2023)
Thoracoabdominal aortic aneurysms (TAAAs) are complex and if untreated have high mortality and morbidity rates. Open surgical repair is the historical treatment approach; however, postoperative complications remain high with spinal cord ischemia notably one of the more serious and common complications. The avoidance of thoracotomy or laparotomy with the advent of endovascular aortic repair (EVAR) and thoracic endovascular aortic repair (TEVAR) have decreased the morbidity and mortality with TAAA repair, especially in patients with significant comorbidities such as a history of aortic surgery, underlying cardiac disease, and chronic obstructive pulmonary disease. Endovascular treatment options have grown to include fenestrated EVAR, multibranched EVAR, and physician-modified fenestration stent grafts. These techniques have achieved lower mortality rates than traditional open repair, but complications such as limb ischemia, spinal cord ischemia, and long-term durability must be considered. This review provides an overview of the most common endovascular techniques for TAAAs as well as short- and midterm outcomes.
Keywords: thoracoabdominal aortic aneurysms; endovascular repair; fenestrated EVAR; branched EVAR; physician-modified fenestrated stent graft